Rancang Bangun Purwarupa Perangkat Wearable Headset untuk Pengukuran Sinyal Listrik pada Otak - Suprijanto; Ayu Gareta R.; Fauza K. Masyhuroh; Siti Maisaroh (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Nowadays, brain signal measurement devices or Electroencephalogram (EEG) are used not only for medical purposes but also for other applications, such as video games (in virtual reality) and biofeedback simulator. A wearable, easy to use and configure, wireless and open system EEG are now very important for those applications. This paper will discuss the design of a wearable and wireless EEG headset. The EEG headset is a bamboo-based headset which was designed with adjustable electrodes positioner to fit the headset with various sizes of head. Other features included in the design is the ability to reduce motion artifacts by adding springs on the electrode’s holder. Four healthy subjects were included during the performance testing of the headset. The performance was tested by comparing the correlation coefficient of the acquired data using headset with the one recorded without headset in frequency domain. The results show that the wearable EEG headset prototype is more robust in minimizing the effect of head movement. It is indicated by higher average value of the coefficient correlation in the EEG recording with headset.